Fonte, fiume, selva. La Riviera del Riso prima e dopo Matteo Maria Boiardo - Corrado Confalonieri (Parole Rubate, 2020)
This paper examines both the sources and the reception of the Laughing Stream episode in Matteo Maria Boiardo’s "Inamoramento de Orlando". In regard to the sources, it restates the importance of the Roman de la Rose for the reshaping of a place whose name comes from Pomponius Mela and Petrarch. With respect to the reception, the essay focuses on the "Gerusalemme Liberata", first debating the reasons why scholars have so far underestimated the relation between Boiardo and Tasso and then arguing that the Laughing Stream is one of the models for the forest of Saron in Tasso’s poem.